Soil Compaction in Oil Palm (Elaies guineensis Jacq.) Plantations: A literature review - Tati Maharani; Adelina Maryanti; Sri Mulyani; Salmita Salman; Ilma Satriana Dewi; Tri Nopsagiarti (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2026)
Soil compaction is becoming a serious issue in oil palm plantations due to the escalating mechanization and more intensive field practices. This review consolidates studies into the source, effects and remediation of compaction in order to gain an insight into how soil degradation affects oil palm growth and yield. A systematic review was conducted of studies in tropical and subtropical systems that applied field experiments, geostatistical mapping, and below-ground soil biological analyses. The results indicate that compaction is primarily influenced by mechanism lightening intensity, texture and water status resulting in an increase of bulk density and penetration resistance as well as a reduction of porosity. Even though root biomass reduction and root structural modification frequently take place in compaction treatments, yield response is not always detrimental, partial compensation has been demonstrated by others through acclimation of roots altering growth. Mechanical subsoiling, biological amendments and controlled traffic farming were the most effective mitigation options, but their long-term effects and interactions with soil microbiota are still unknown. Additionally, compaction changes the soil microbial community and chemistry, which results in nutrient cycling disturbances and greenhouse gas emissions. On the whole, these syntheses point to requirements for more integrated ecological and long-term management strategies, combining both physical and biological aspects of soil health and oil palm productivity in tropical landscape overall.